(untitled) (Bangladesh Journal of Pharmacology, 2016)
Leaves of Loranthus pulverulentus have been used ethnically in Pakistan for controlling blood glucose levels. The present study was designed to investigate the anti-diabetic and anti-oxidant potential of the methanolic extracted fractions of L. pulverulentus obtained from two different hosts viz. Dalbergia sissoo and Populus nigra. The acute study demonstrated that L. pulverulentus (D. sissoo) leaves possess significant blood glucose lowering effect whereas L. pulverulentus (P. nigra) was didnt significantly decreased blood glucose levels. The n-butanol fraction of L. pulverulentus (D. sissoo) also significantly increased in vivo total anti-oxidant activity on eighth day after treatment and blood glucose levels were significantly reduced (%46.7) when compared to the control diabetic group (%?198.1) and metformin treated group (%?25.9). Leaves of L. pulverulentus (D. sissoo) have good margin of safety as therapeutic index is 3.5. This study provides scientific evidence that leaves of L. pulverulentus (D. sissoo) possess potential anti-diabetic activity whereas L. pulverulentus (P. nigra) was not found effective in diabetic illness.